The Relationship Between the Percentage of Skeletal Muscle (SMP) and the Emergence of Degenerative Diseases (Hypertension) in Posyandu for the Elderly Mugi Sehat - Ghani, Farid; Siwi, Adiratna Sekar; Dewi, Pramesti (PROMOTOR, 2024)
Degenerative disease is a condition of continuous decline in body function with increasing age. Hypertension is a degenerative disease that is often suffered by the elderly. The aging process results in changes in body composition, often without being accompanied by weight changes. Increasing age in the elderly will experience functional limitations caused by changes in body composition, one of which is the Percentage of Skeletal Muscle. The purpose of this study was to determine the relationship between the percentage of skeletal muscle and the emergence of degenerative diseases (hypertension) in the elderly at the Mugi Healthy Elderly Posyandu. The instruments in this study used a Digital Sphygmomanometer to measure blood pressure and an Omron Karada Scan Body Composition Monitor Model HBF-375 to measure Skeletal Muscle Percentage. This research method uses a cross-sectional research design. The sample in this study is 58 people. The research was conducted at the Mugi Sehat Elderly Posyandu in the working area of the 2022 UPTD Kembar I health center in May-June 2023. The sampling technique in this study uses total sampling and data analysis using the Spearman Rank test. The results of this study from the bivariate analysis showed that there was no relationship between the Percentage of Skeletal Muscle and the emergence of degenerative diseases (hypertension) in the elderly at the Mugi Healthy Elderly Posyandu, namely the Percentage of Skeletal Muscle with hypertension P value = 0.576 (CC=-0.075).